BATIK: NILAI-NILAI PENDIDIKAN DALAM KEGIATAN MEMBATIK DI SEKOLAH DASAR - Eka Yulyawan Kurniawan (Indonesian Journal of Elementary Education (IJOEE), 2023)
Batik is Indonesia's cultural wealth from time to time. Batik is one of Indonesian cultural arts that is well known to foreign countries, there are educational values in batik activities, in the world of education the introduction of Batik already exists from the elementary school education level, but few teachers are able to provide practical experience of batik. Therefore, teachers in elementary schools must be equipped with experience and knowledge of batik practice through training so that they can teach students. This study uses a qualitative method, where the teacher learns while doing (Learning By Doing). The learning process starts from the introduction of Batik and the educational values in it, how to make batik patterns, to coloring. Hopefully many elementary school teachers can play an important role in contributing to the preservation of Batik art.Keywords: Batik, Educational Value, Elementary School